2022
DOI: 10.1073/pnas.2114558119
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-mediated natural and manipulated population collapse in an invasive social insect

Abstract: Significance Invasive social insects are among the most damaging of invasive organisms and have proved universally intractable to biological control. Despite this, populations of some invasive social insects collapse from unknown causes. We report long-term studies demonstrating that infection by a microsporidian pathogen causes populations of a globally significant invasive ant to collapse to local extinction, providing a mechanistic understanding of a pervasive phenomenon in biological invasions: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Pathogens have been hypothesized to cause boom‐and‐bust dynamics in introduced species, including invasive ants (LeBrun et al, 2022; Lester & Gruber, 2016; Simberloff & Gibbons, 2004). Outside their native range, many invasive ants such as the Argentine ant ( Linepithema humile ) form large, dense, cooperating unicolonial populations that comprise a great number of nests (Holway et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens have been hypothesized to cause boom‐and‐bust dynamics in introduced species, including invasive ants (LeBrun et al, 2022; Lester & Gruber, 2016; Simberloff & Gibbons, 2004). Outside their native range, many invasive ants such as the Argentine ant ( Linepithema humile ) form large, dense, cooperating unicolonial populations that comprise a great number of nests (Holway et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, genetically differentiated populations of green peach aphids (Myzus persicae Sulzer), Mediterranean fruit ies (Ceratitis capitata Wiedemann), and mountain pine beetles (Dendroctonus ponderosae Hopkins) have all been shown to vary in their susceptibility to pesticides and stress tolerance [49][50][51]. Recently, the application of a fungus-like microsporidian pathogen was found effective at decreasing and in some instances eliminating TCA populations [52][53][54]. Further investigation is required into the effectiveness of this biopesticide on other TCA populations.…”
Section: Discussionmentioning
confidence: 99%
“…In males captured in 2017 and 2018, no pattern was immediately evident despite a significant difference in infection load between trap years, trap days and the interaction between the two as shown in figure 6. While the results may be statistically significant, insect pathogens, like human pathogens, are known to vary annually and seasonally (Abdel-Baki et al 2009, Herren et al 2020, LeBrun et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…While we cannot confirm the reason for the discrepancies in Nosema sp. prevalence, it has previously been observed that, in general, the low virulence of microsporidian pathogens allows for an increase in prevalence in the population over time (Biganski et al 2021, LeBrun et al 2022). A possible explanation for the difference in results may be that during the range expansion by the western bean cutworm, not all individuals were infected with the microsporidian parasite.…”
Section: Discussionmentioning
confidence: 99%